IMPLEMENTASI KEBIJAKAN PENCEGAHAN DAN PEMBERANTASAN PENYALAHGUNAAN DAN PEREDARAN GELAP NARKOBA (P4GN) OLEH BNNP DAERAH ISTIMEWA YOGYAKARTA - Ecep Endang Komara; Syakdiah Syakdiah; Retno Kusumawiranti (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2021)
Abstract: DIY ranks first in drug trafficking among students, in general Jogja is in the top 8, the government has issued a P4GN policy according to INPRES No. 12 of 2011 but the implementation has not been maximimized therefore BNNP DIY as the National Narcotics Agency functions as the executor of the implementation of P4GN policy.Â  In implementing P4GN policy among students in Yogyakarta, BNNP DIY as a representative of BNN in the regions do not make policies and programs according to regional conditions. However, BNNP as an extension of BNN is given the authority to determine the priority targets of the program through the implementation of technical guidance by inviting institutions and agencies that are within the scope of DIY. Implementation of the P4GN policy among students has not gone well, because the factors that are considered the most urgent in an implementation have not been fulfilled properly, especially in the field of human resources and budget availability, suggestions for adding extension agents in the prevention section and adding to the existing budget at BNNP DIY